Diagnostic and prognostic values of HCG15 and morrbid in acute myocardial infarction - Huang, Min; Wu, Bohua; Ou, Xiuxia; Sun, Shuo; Han, Kedong; Li, Lijian; Liang, Haiyan; Qiu, Chunchan; Xu, Qingbo (Frontiers in Pharmacology, 2024)
Acute myocardial infarction (AMI) represents the gravest manifestation of ischemic heart disease, with the primary cause of mortality and morbidity worldwide. Although timely and accurate diagnosis of AMI is crucial in clinical practice, they are impeded by the limitation of current biomarkers. We aimed to explore the potential predictive value of two novel long noncoding RNA (lncRNA) HCG15 and Morrbid in AMI diagnosis and prognosis.We measured the lncRNA levels in the blood samples of 412 AMI patients and 111 healthy volunteers with the RT-PCR method. Receiver operating characteristic (ROC) curves were plotted to access the diagnostic value of selected lncRNAs. Restricted cubic splines (RCS) and the Kaplan-Meier method were utilized to examine the predictive value of the selected lncRNAs in AMI diagnosis.ROC curves identified an acceptable diagnostic value of HCG15 and Morrbid (AUC for HCG15: 0.937; AUC for Morrbid: 0.940). RCS and Kaplan-Meier analysis revealed the cutoff value of 3.6 for HCG15 and 4.0 for Morrbid have a good predictive value in MACCE within 12 months once AMI was diagnosed (P-value for HCG15: p = 0.025; P-value for Morrbid: p < 0.0001).HCG15 and Morrbid were confirmed as promising lncRNA biomarkers for both diagnosis and prognosis of AMI in this study. Additionally, their importance of application in real-world clinical practice and underlying mechanisms in AMI diagnosis and prognosis remain to be explored.